Metabolic reallocation in spinal cord oligodendrocytes drives chronic pain in mice through neuronal Aβ 42 production - Yannick Fotio; Saeed Al Masri; Zechuan Shi; Johnny Le; Sudeshna Das; Varvara I. Rubtsova; Alex Mabou Tagne; Cholsoon Jang; Vivek Swarup; Daniele Piomelli (Science Translational Medicine, 2026)
Recent evidence implicates a metabolic switch in afferent spinal circuits as a key driver of the transition from acute pain– to chronic pain–related behaviors in mice after tissue injury, yet the cellular substrates and functional consequences remain incompletely defined. Using a combination of pharmacological and genetic approaches, we investigated whether metabolic reprogramming in spinal cord cell populations constitutes a causal mechanism linking peripheral injury to the progression to pain chronicity. After peripheral injury induced by a hindpaw formalin injection in mice, single-nucleus RNA sequencing (snRNA-seq) revealed that spinal oligodendrocytes down-regulated transcripts for myelin protein synthesis and up-regulated transcripts important for lipid biosynthesis. Comparative lipidomics showed that this resource reallocation after peripheral injury was associated with disrupted spinal myelin composition. Moreover, axonal integrity was compromised, causing neuronal accumulation of amyloid precursor protein, enhanced β-site amyloid precursor protein–cleaving enzyme 1 (BACE1) expression, and increased insoluble amyloid-β 42 (Aβ 42 ) during a critical temporal window for the transition to pain chronicity. Blocking Aβ 42 production by BACE1 inhibition or clearing Aβ 42 by intrathecal 4G8 monoclonal antibody injection prevented the emergence of persistent pain after hindpaw formalin injection. Oligodendrocyte-specific deletion of N -acylethanolamine acid amidase, a key regulator of cell metabolism and pain, prevented Aβ 42 release and chronic pain development induced by formalin injection or sciatic nerve ligation. These findings uncover an unexpected mechanistic link between chronic pain and amyloid pathology and identify the NAAA→Aβ 42 pathway as a target for disease-modifying intervention.